Application of nanomaterials for the treatment of glioblastoma - Hu, Yufei (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Glioblastoma, as the most severe type of primary brain tumor, presents great difficulties in treatment due to its fast-growing nature, recurrence, and resistance to typical treatment methods. A particularly hard challenge is the blood-brain barrier (BBB), which makes it difficult for many drugs to reach tumor regions in enough amounts for the treatment to work well. Nanomaterials may provide one possibility for enhancing immunotherapy in glioblastoma by improving the delivery of drugs, helping them cross the BBB, and adjusting immune responses. This research looks at recent progress in using nanomaterials for glioblastoma treatment, focusing on types of organic and inorganic nanoparticles. Organic nanomaterials like lipid-based or polymer nanoparticles have the potential to deliver drugs directly to the tumor, with longer-lasting effects. Inorganic nanomaterials, such as magnetic nanoparticles, iron oxide ones, or gold nanoparticles, have been shown to be helpful for hyperthermia and photothermal therapy, as well as improving radiotherapy. These nanomaterials can be used alone or as vaccine adjuvants, providing practical options for getting through the BBB and delivering therapeutic agents to the tumor site. The integration of nanomaterials into glioblastoma treatments holds a certain potential to create better treatment plans for glioblastoma cases.